Spectral Studies of UV and Solar Photocatalytic Degradation of AZO Dye and Textile Dye Effluents Using Green Synthesized Silver Nanoparticles - R. Mariselvam; A. J. A. Ranjitsingh; P. Mosae Selvakumar; Abdullah A. Alarfaj; Murugan A. Munusamy (Bioinorganic Chemistry and Applications)
The photocatalytic degradation of the chemical dye AZO and dye effluents in different time duration has been investigated using biologically synthesized silver nanoparticles. Dye industry effluents and AZO dye undergo degradation to form harmless intermediate and colourless products following irradiation by UV and solar light in the presence of green synthesized silver nanoparticles. The degree of degradation was tested under the experimental conditions such as PH, temperature, and absorbance of the dye in UV and solar light was measured. The degradation was higher in the UV light source than in the solar light source. Green synthesized silver nanoparticles in the UV light source were found to expedite the dye degradation process.